Does ESG report greenwashing increase stock price crash risk? - Guangrui Liu; Hao Qian; Yong Shi; Yu Zhang; Fengyuan Wu (China Journal of Accounting Studies (CJAS), 2024)
From the perspective of non-financial information greenwashing, this paper investigates the impact mechanism of environmental, social and governance (ESG) report greenwashing on stock price crash risk. The results indicate that ESG report greenwashing increases the stock price crash risk. In high earnings management companies, ESG report greenwashing is positively correlated with stock price crash risk, and ESG report greenwashing and earnings management are complementary. Further analysis shows that better internal and external corporate governance can suppress the impact of ESG greenwashing. In addition, in the voluntary disclosure and private enterprise samples, ESG report greenwashing has a greater impact on the stock price crash risk. Mechanism analysis found that the greenwashing of ESG reports intensified the information asymmetry, which increased the stock price crash risk. Overall, our evidence is consistent with the masking effect of socially responsible information, and that ESG greenwashing increases the stock price crash risk.
Keywords: 650; stock price crash risk; Environmental; social and governance; environmental; social and governance report; greenwashing; social responsibility information